Solutions to Preventing Mistake in Building Electrical Installation and Maintenance In Urban Area Based on Skills Training - Jaja Kustija; Alif Ulfa Afifah; Hasbullah Hasbullah; Irgi Surya (Institut Teknologi Nasional, Bandung, 2023)
Electricity plays an important role in the functionality of a building. To ensure the required electrical competencies are met, it is essential to provide appropriate training. Therefore, this community service program based on the needs of the assisted village aimed at providing training to potential dropout youths, equipping them with skills in operating and maintaining building electrical installations, enhancing awareness regarding the importance of proper and correct electrical installations, and fostering energy-independent village. The training included several stages namely preliminary study, planning, implementation, mentoring, monitoring and evaluation. The results of the activity showed that the participants of the training obtained operational as well as building electrical system maintenance skills. These acquired competencies led to the improved standard of living, increased welfare, and the prevention of hazards resulting from errors in electrical installation and maintenance within the village of Giri Mekar. The outcome of this community service activity was that in the assisted village a number of skilled installer cadres had emerged, possessing skills in the operation and maintenance of building electrical installation systems.